Improvements in the development of silicon nitride inserts using hybrid microwave energy for machining Inconel 718 - Ariff, Tasnim Firdaus; Mohamed, Nur Maizatul Nasyiin; Binafif, Abdulaziz Abdullah; Azhar, Ahmad Zahirani; Bahar, Rubina; Karim, A.N. Mustafizul; Amin, A.K.M. Nurul (ESRSA Publications Pvt. Ltd., 2018)
Hybrid Microwave (HMW) sintering is becoming popular for heating ceramics, composites, metals and alloys. It is becoming a trendy research due to its capabilities in saving time, energy and money, increasing efficiency and productivity,improving mechanical and structural properties. Silicon Nitride (Si3N4) is widely used as a cutting insert for machining cast iron, hard steel and nickel based alloys. It is mass produced by traditional powder technology. This research aims to increase the tool life of the Silicon Nitride inserts by enhancing the mechanical and structural properties by using Hot Isostatic Pressing (HIP) at 1800°C and followed by hybrid microwave (HMW) post-sintering at 200°C for 10 minutes with the aid of Silicon Carbide powder as susceptor. Three different compositions (88%, 90% and 92% Si3N4) were synthesized in order to find the optimum composition using these techniques. Mechanical and structural properties were analyzed. The combination of HIP+HMW post sintering for just 10 minutes significantly enhanced the density (93-97%TD), hardness (18-22%), compressive strength (2-4%) and produced finer uniform grains particularly for 88% and 90% Si3N4 when compared with HIP samples without any post sintering effect. Hence, the 88% and 90% Si3N4 compositions produced by the combination of HIP+HMW post sintering are potentially suitable candidates for machining hard materials such as Inconel 718.